Pandemic and State Debt Settlement Scenarios - Endang Rudiatin; Wibowo Hadiwardoyo (Universitas Muhammadiyah Jakarta, 2021)
Many countries have been forced to increase their debt to face the Covid-19 pandemic with the assumption that it will be settled once the economy returns to normal. But the pandemic is still ongoing even though it has passed a year and a half. The emergence of new variants of the Coronavirus has forced the re-imposition of even stricter restrictions. The direct result is a budget deficit, as state revenues fall, while spending rises. The longer the restrictions last, the larger the deficit will be, so it is still very possible for additional new debt to occur. With the increasing number of debts, scenarios are needed to solve them, including the worst option. This study presents various possibilities that a country can do to pay off debts that are difficult to repay, based on the experiences of several countries that have experienced it in the past. It is also a possible new breakthrough alternative, despite facing complex domestic political challenges. The alternative is based on phenomenological research in virtual communities through the internet on the phenomenon of pandemics and state debt. The results show common actions by the State in overcoming the economic crisis, namely, increasing tax rates, reducing salaries and facilities for employees/officials, selling (shares) of State-Owned Enterprises (BUMN). Then unpopular alternative offers such as leasing certain islands/areas to foreign parties, and other breakthroughs.